Flavonoids and other constituents with insulin secretion activity from Pseudarthria hookeri. (September 2016) - Tchamgoue, Joseph; Hafizur, Rahman M.; Tchouankeu, Jean Claude; Kouam, Simeon F.; Adhikari, Achyut; Hameed, Abdul; Green, Ivan R.; Choudhary, Mohammad I.
Graphical abstract: Highlights: Three new flavonoids were isolated from Pseudarthria hookeri . The structures were elucidated on the basis of chemical and spectroscopic data. The isolated compounds displayed potent activity with insulin secretion. Abstract: Three new flavonoids viz., pseudarflavones A (1 ) and B (2 ) and 6, 7-(2″, 2″-dimethylchromano)flavanone (3 ), were isolated from Pseudarthria hookeri together with thirteen known compounds: boeravinone L (5 ), gancaonin P (4 ), dorsamin F (10 ), emodin (6 ), 6-prenylpinocembrin (7 ), hiravanone (11 ), dorsmanin I (12 ), 6, 8-diprenyleriodictyol (13 ), 6-prenyl-3′-methoxyeriodictyol (14 ), oblonginol (15 ), orobol (16 ), protocatechuic acid (17 ) and α-terthienyl (18 ). Their structures were elucidated by IR, MS, 1D and 2D NMR spectroscopic techniques and by comparison with data reported in the literature. Chemical transformations were also employed to confirm some assignments. The insulin secretory activity of compounds (1, 3 −18 ) was evaluated on isolated mice islets. Compounds (1, 3, 5 and12 ) showed a mild effect on glucose stimulated insulin secretion while compounds (4, 10, 14 and16 ) were found to display moderate insulin secretory activities of 247.5%, 404.8%, 350.7% and 291.8% respectively, in comparison to the control. The tested compounds showed no toxic effect on MIN-6 and 3T3 cell lines up-to 400 μM. These results demonstrated that compounds (10 ) and (14 ) showed a potential to be considered as new insulin secretagogues and that further development of their derivatives may increase their insulinotropic potential.